Obowiązki stron w umowie o pracę w kodeksie zobowiązań z 1933 roku - Baszak, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Alongside white-collar workers, labourers were the most significant group of workers in the Second Polish Republic. In 1928 the legislator decided to issue a special regulation concerning employment contracts for labourers. The provisions of the regulation were not rescinded even by the entry into force of the Code of Obligations of 1934, Articles 441–477 of which regulated employment contracts. The provisions of the Code of Obligations were only subsidiary to the provisions of the regulation.In the article the author discusses the legal provisions concerning employment contracts in 1928–1939, i.e. when the Labourer Employment Contract Regulation and Code of Obligations were in force. He examines the provisions of the Labourer Employment Contract Regulation in connection with the White-Collar Employment Contract Regulation and the provisions of the Code of Obligations concerning employment contracts.
Keywords: II Rzeczpospolita; kodeks zobowiązań; umowa o pracę